Evaluating performances of Malaysian banks in RAROC and EVA framework: a new perspective - Saha, Asish; Ahmad, Nor Hayati; Siew, Goh Yoke (2014)
As Malaysian Banks are stepping into the Basel-III era, a close look at their performance on risk adjusted basis using RAROC and EVA would throw significant light on their relative strengths and weaknesses.Following the Asian Financial Crisis, Bank Negara Malaysia (BNM) fostered strategies to strengthen and an orderly development of the financial system in the country.Under the said initiatives, the banking system in the country underwent restructuring, mergers & consolidation and rationalisation during 1998-2000.The regulatory framework of BNM throughout the decade of 2001-10 was mainly centered on capitalization, risk management and governance practices in banks. It is now nudging the banks to graduate to the more stringent capital and liquidity requirements in the Basel-III era.Though numerous studies have evaluated the performances of Malaysian commercial banks in terms of efficiency and productivity gains before and after the merger and also at various phases during the last decade, no study has so far been reported assessing their performances using RAROC and EVA framework. Present study, fills up this enormous gap in the literature and report its findings in its evaluation of the performances of eight commercial banks during 2001 to 2012 period.The findings of the study would be of keen interest to the policy planners, investors and researchers alike.